A study on the clinical and social aspects of polycystic ovarian syndrome in women of reproductive age group conducted at a specialized medical facility - Sekhasaria, Priyanka; Agrawal, Akanksha; Chundawat, Rama Singh; Sharma, Rajrani; Jakhar, Balveer (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Polycystic ovarian syndrome (PCOS) is seen as a complex illness that can present in women of various ages, including teenagers and post-menopausal women, not just those of childbearing age. The prevalence of PCOS in India ranges from 3.8% to 22.4% in most studies. The updated diagnostic criteria in Rotterdam consensus conferences now require the presence of two of the following: irregular periods, signs of excess male hormones, polycystic ovaries on ultrasound, and ruling out other possible causes like congenital adrenal hyperplasia, androgen-secreting tumors, and Cushing syndrome. Methods: The research was carried out on women in the reproductive age category who have PCOS and were visiting the gynecology department at Pacific medical college and hospital in Udaipur. This is prospective comparative study/descriptive cross-sectional study. A total of 150 women were part of the sample. Research was conducted to investigate the correlation between PCOS and the socio-demographic characteristics of the patient. Results: The mean age of participants in the research was 21.68 years, with a deviation of 4.2 years. Approximately 72% are burdened by excess weight, 22% suffer from acne, 21% encounter fertility issues, 6% have amenorrhea, 80% struggle with oligomenorrhea, and 26% are classified as obese. Acne is present in 23% of the participants in the research. Around 38% of people showed signs of hirsutism. Conclusions: Research revealed a notably high occurrence of PCOS among females aged 21 to 30, with an average age of 23. These females were from a moderate socio-economic background and resided in urban areas, with most of them being students and homemakers leading sedentary lives. The most common clinical symptoms of PCOS in women were noted to be oligomenorrhea, weight gain, infertility, hirsutism, and acne.